(untitled) (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2025)
This study aims to analyze the strategies used by teachers in improving the speaking skills of grade VIII students at SMP Swasta Muhammadiyah 21 Serbelawan. The background of this study is based on the importance of speaking skills in English as one of the main skills in communication, as well as the challenges often faced by students and teachers in the process of learning speaking. This study uses a qualitative approach with a case study method. Data were collected through direct observation, in-depth interviews with teachers and students, and documentation such as the Lesson Implementation Plan (RPP). The results of the study showed that teachers faced various obstacles such as low student self-confidence, limited vocabulary and pronunciation mastery, and lack of understanding of the material presented in English. To overcome this, teachers implemented various strategies, including the use of audio-visual media (music and video), a bilingual approach in explaining the material, and the implementation of speaking tasks involving activities such as storytelling, role-play, and presentations. These strategies have been shown to help increase student participation and build their confidence in speaking English. This study is expected to contribute to the development of more effective speaking teaching strategies at the junior high school level